The Polish Academic Profession: What We Know, What We Do Not Know, and What We Would Like to Know – from a European Comparative Perspective - Kwiek, Marek (My University, 2015)
Academic attitudes (and beliefs) and academic behaviors are explored: how Polish academics work, what they think (about their work)? Four major comparative themes are discussed: (1) Internationalization in research and research productivity (Polish “internationalists” vs. Polish “locals”), (2) University governance (a powerful Ivory Tower university model prevailing in Poland; Polishe universiites as a professorially coordinated “republic of scholars”). (3) The Polish research elite (highly productive academics: who they are, how they work?, and (4) Intergenerational patterns of academic work – Polish academics under 40 - What we know, what we do not know, and what we would like to know – about each theme. Within each theme – the data are examined in the context of 10 Western European comparator countries: Austria, Finland, Germany, Ireland, Italy, the Netherlands, Norway, Portugal, Switzerland, and the UK.
Keywords: Polish higher education; Polish academics; academic profession; Polish academic profession; internationalization; research performance; research productivity; publication productivity; research elite; highly productive academics; high research performance; research performance; young academics; academics under 40; Polish universities; European universities; international cooperation; international collaboration; intergenerational patterns; publishing patterns; university governance; Humboldtian model; Ivory Tower; academic collegiality; non-performers; non-publishers; European non-publishers; EUROAC project; CAP project; CAP dataset; university reforms; higher education reforms